USING “STORYBIRD” FOR TEACHING NARRATIVE WRITING - Rini Anita (Universitas Negeri Padang, 2016)
Major changes in Information and Communication Technology (ICT) have made lecturers need to come up with an idea of bringing it into the classroom. Indeed, lecturers may not just neglect the impact of new technologies and fail to incorporate them in their teaching practice. One big evolution in classroom technology has been in the development of using webtools for teaching writing. Storybird; a website 2.0 tool, is an excellent new media for teaching narrative writing. It will not only highly motivate the students to write in English and other languages but also it gives an opportunity for the students to control their learning experiences by means of technology device. Beside Storybird can be easily accessed by the students using their netbook, smartphones, or other devices. Thus, this paper deals with the use of Storybird in teaching narrative writing.